Reference Price Shifts and Customer Antagonism: Evidence from Reviews for Online Auctions - Tobias Gesche (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Using data from a large-scale sales campaign on eBay, I show that successful auction customers punish the seller through unfavorable public feedback when they later learn discover a cheaper fixed-price offer. The probability of receiving such feedback is four times bigger for auctions than for fixed -price sales of the same item from the same seller. Remarkably, this probability is increasing in the auction price, even though auction customers actively shaped this price themselves. In line with an explanation based on ex-post reference price shifts, this price effect is concentrated in a period during which reference prices were particularly salient because customers information about them, but not about idiosyncratic transaction features (e.g. quality), could change. Consistent with the reference price explanation, the difference in unfavorable feedback between auctions and fixed-price sales is also concentrated in this period and drops to a quarter of its initial size afterwards.
Keywords: D44; D91; M31; 330; customer antagonism; pricing; reference prices; online reputation; eBay